The Evaluation of The Use of a MultiAgent System Coordination Mechanism to Support Emergency Operations - Katende, Emmanuel D. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2015)
This short-paper presents an initial overview of a research work that deals with emergency operations in urban cities using MultiAgent System Coordination mechanism. We presented first the emergency scenario in the state of Santa Catarina in Brazil, citing some main challenges encountered in such cases, and thus showing how it is important to find solutions to cope with emergencies. Following, we analysed some works in the literature that present some solution for emergency cases, and show some issues in such works that need more studies. Lastly, we list the likely steps of the solution method to be implemented in future works, as a potential solution that can manage emergency operations considering the observations presented in the state of the art.